THE EFFECTS OF LEARNING MODELS AND LINGUISTIC INTELLIGENCE ON THE PERSUASIVE WRITING SKILL - Yusri, Yusri; Emzir, Emzir (IJLECR (International Journal of Language Education and Cultural Review), 2017)
The objective of this study is to know the effects of learning models (problem solving and project based learning) and linguistic intelligence on the students of persuasive writing skill of the fourth semester students of English Department, State Polytechnic of Sriwijaya Palembang, in the academic year of 2016-2017. The writer used linguistic intelligence test and persuasive writing test to collect the data. The data was analyzed statistically by using two-factor ANOVA at 0.05 significance level. The results of this study showed that (1) The students’ persuasive writing skill taught through problem solving was higher than those who were taught through project based learning. (2) There was interaction effect between learning models and linguistic intelligence toward persuasive writing skill of the fourth semester students of English Department, State Polytechnic of Sriwijaya Palembang. (3) The students’ persuasive writing skill who were taught by using problem solving and having high linguistic intelligence is higher than those who were taught through project based learning and having high linguistic intelligence. (4) The students’ persuasive writing skill who were taught through problem solving and having low linguistic intelligence is lower than those who were taught through project based learning and having low linguistic intelligence.